Acute Toxicity Test of Mulberry Leaf Extract (Morus rubra L) as a Basic Ingredient of Candida Albicans Antifungal on Rattus Norvecigus - Nina Hidayatunnikmah; Anik Latifah (EMBRIO: Jurnal Kebidanan, 2024)
Previous research on the effectiveness of mulberry leaves in the growth of candida albicans showed that C. albicans is inhibited in vitro. Mulberry leaf extract is used as a basic ingredient for treatment. In addition to being tested for effectiveness, testing is needed to ensure the level of acute toxicity in experimental animals in determining toxicity levels. The study aimed to test the acute toxicity of mulberry leaf extract on Rattus Norvecigus media in determining the level of toxicity before becoming the basic ingredient of VVC antifungal. The research method uses an experimental laboratory post-test-only control group design with a 9 Rattus Norvegicus media. The average dose is not lethal using LD50 values. Research analysis using ANOVA is One Way to determine the difference in the average weight change of experimental animals. The study's results did not show any deaths of experimental animals or toxic symptoms in administering mulberry leaf extract doses of 0 mg, 100mg, 1000 mg, 1600mg, 2900mg, 5000mg. LD50 value more than 8g/kg BW, included in the non-toxic category (5-15 g/kg BW). The ANOVA statistical test showed a P-value of 0.781 more than a P-value of 0.05, that is, there was no difference in the average change in body weight in the experimental animal group given different treatment doses in each group. The research concludes that mulberry leaf extract does not show a lethal dose of acute toxicity, so it is safe to use as a basic ingredient in treatment sourced from natural ingredients.